National Medical Research Center for Pulmonology: experience of the first year of work and development prospects: A review - Sergey N. Avdeev; Nikolay A. Voznesenskiy; Zamira M. Merzhoeva; Lidia Yu. Nikitina; Zelimkhan G.-M. Berikkhanov (ZAO "Consilium Medicum", 2023)
The article highlights the main activities of the National Medical Research Center for Pulmonology of the Sechenov University. The main results of clinical, analytical and educational activities are outlined. The prospects for the development of the pulmonological service of the Russian Federation, current problems and their solutions are determined.